Influência do tratamento superficial da nanocarga nas propriedades mecânicas de curta e longa duração de um nanocompósito de PEEK/nHA - Marcomini, André Luís (Universidade Federal de São Carlos, 2014)
In this dissertation the mechanical properties of short and long term of PEEK/nHA nanocomposites with potential application as orthopedic implants were studied. The nanohydroxyapatite (nHA) was surface-treated with the coupling agent aminoethylaminopropyltrimethoxysilane (AEAPTS). After treatment, the nanoparticles were mixed with the polymeric matrix of poly (ether ether ketone) (PEEK) in a twin screw extruder. Subsequently specimens of the nanocomposite were injection molded. These specimens were subjected to mechanical tests to have their properties compared with the pure polymer and the nanocomposite with the pure nHA. First, tensile tests were conducted; through these analyses, it was found the stress and strain at break increased. The presence of the silane increased the fatigue life of the nanocomposite suggesting a higher interaction between the matrix and the nanofiller. The impact tests confirmed the higher resistance of the sample with silanized nHA. It was concluded that the silanization of the nHA was effective, strengthening the interface PEEK/nHA; however, silane molecules also plastified the polymer matrix. The injected test specimens were subjected to annealing. The objective was to determine how the increase in crystallinity induced by annealing influenced the mechanical properties. After the annealing, the presence of the silane did not cause significant changes in the mechanical behavior of the material. Analysis of scanning electron microscopy (SEM) and dynamic mechanical analysis (DMA) were done in order to characterize the structure of the nanocomposites. The morphology observed in the micrographs was correlated with the dynamic mechanical properties. It was concluded that the nanocomposite with silanized nHA besides having elastic modulus behavior similar to natural bone, also had a more homogeneous structure than the nanocomposite with pure nHA.
Influence of surface treatment of nanoparticle in short and long term mechanical properties of PEEK/nHA nanocomposite
Keywords: PEEK; Nanohidroxiapatita; Aminosilano; Fadiga; CIENCIAS EXATAS E DA TERRA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS